PENYULUHAN KESEHATAN GIGI DENGAN MEDIA BOOKLET DAN PELATIHAN MENYIKAT GIGI PADA PASIEN DIABETES MILITUS DI WILAYAH KERJA PUSKESMAS IV DENPASAR SELATAN TAHUN 2021 - anak agung gede agung; i nyoman wirata (Jurnal Pengabmas Masyarakat Sehat, 2022)
Statistics show that dental and oral disease affects almost everyone, including people who have diabetes mellitus. Tooth brushing behavior is one of the most important and effective health behaviors for the maintenance of dental and oral health by preventing plaque from forming on the teeth. Brushing your teeth will reduce the contact of sucrose and bacteria so that it can prevent caries. This Community Service Method is this service is carried out by providing counseling and training on brushing teeth. The measurement of knowledge and behavior of brushing teeth was carried out by pre-posttest. Furthermore, the collected data were analyzed descriptively and analytically. Namely an increase in knowledge about dental and oral health after community service activities, namely before counseling most of the knowledge targets were categorized as lacking and after counseling their knowledge became good category. After the tooth brushing training activity, there was an increase in tooth brushing behavior from the poor category to the good category. The results of the statistical test showed that there was a significant difference in the knowledge, and tooth brushing behavior before and after the counseling and brushing training activities with a significant value of 0.000 (p 0.05). It is recommended to holders of non-communicable disease programs, especially chronic disease programs at puskesmas and related parties, to continue to provide promotive services in the field of dental health on an ongoing basis.